Clinical features of pneumococcal meningitis - Aman, Mehdi Al; Onishchenko, T.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2015)
Objective: to evaluate the clinical features of pneumococcal meningitis (PM) and pneumococcal meningoencephalitis ( PME ) based on Zaporozhye Regional Hospital for Infectious Diseases ( ZRHID). It made clinical - laboratory monitoring in 26 patients with PM and PME. The evaluated group was dominated by middle aged persons - 9 (34,6%) and older - 11 (42,3%). Most of the patients (21-80,8%) the disease has developed against the background of severe comorbidity. Severe course of the disease have been reported in 24 (92,3%), moderate in 2 (7,7%) patients. Mortality rate was 15,4%.